2021
DOI: 10.3390/pharmaceutics13030301
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Best Predictor of Phenobarbital Pharmacokinetics to Use for Initial Dosing in Neonates?

Abstract: Phenobarbital is a first-line treatment of various seizure types in newborns. Dosage individualization maximizing the proportion of patients with drug levels in therapeutic range or sufficient treatment response is still challenging. The aim of this review was to summarize the available evidence on phenobarbital pharmacokinetics in neonates and to identify its possible covariates suitable for individualization of initial drug dosing. Several covariates have been considered: body weight and height, body surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…Some covariates, such as body weight, height, asphyxia, extracorporeal membrane oxygenation (ECMO), and genetic polymorphisms, were considered to affect drug dosing. As reviewed in Sima et al, doses at the suggested lower limit should be preferred in patients with severe asphyxia, while the upper limit should be targeted toward neonates receiving ECMO support [71] .…”
Section: Integration Of Genotype-phenotype Information For Precision ...mentioning
confidence: 99%
“…Some covariates, such as body weight, height, asphyxia, extracorporeal membrane oxygenation (ECMO), and genetic polymorphisms, were considered to affect drug dosing. As reviewed in Sima et al, doses at the suggested lower limit should be preferred in patients with severe asphyxia, while the upper limit should be targeted toward neonates receiving ECMO support [71] .…”
Section: Integration Of Genotype-phenotype Information For Precision ...mentioning
confidence: 99%